TRADISI MENGHAFAL AL-QUR’AN DI PONDOK PESANTREN (Studi Living Qur’an Di Pondok Pesantren Al-Mubarok Mranggen Demak) - Laila Ngindana Zulfa (LP2M, 2018)
The issue of the Qur'an is indeed a topic that never dies in research studies, this is because the Qur'an has the role and function of “Shalihun li kulli zaman wa makan”. It also encourages researchers to always develop research in the Qur'an. In contrast to previous researchers who focused on the study of interpretations and understandings of the Qur'anic text. In this study, researchers try to examine the phenomena that occur in society towards the understanding of the Qur'an. This research is also called the study of the living Qur'an with a focus on the tradition of memorizing the Qur’an among the Santri (Student).Keywords: Rote Tradition, Living Qur'an.